Využití virtuální reality v dynamice vozidel - Mach, Břetislav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem této diplomové práce je využití virtuální reality pro analýzu a zobrazení vozidla a veličin charakterizujících dynamické vlastnosti automobilu. Pro simulaci jsou využity programové nástroje Matlab/Simulink a Virtual Reality Toolbox pro ztvárnění virtuálního prostředí. Vstupem pro simulaci budou změřená nebo vypočtená data.

The aim of this master’s thesis is to use virtual reality to analyze and display the vehicle and the quantities characterizing the dynamic properties of the vehicle. The simulation software tools are used Matlab/Simulink and Virtual Reality Toolbox. The measured or calculated data will the input for the simulation. The dissertation is aimed to create a virtual scene and a dynamic system for the movement of file.
The Use of Virtual Reality in Vehicle Dynamics
Keywords: dynamika vozidla; virtuální realita; simulace; jazyk VRML; program Matlab/Simulink; Virtual Reality Toolbox; vehicle dynamics; virtual reality; VRLM language; the Matlab/Simulink; Virtual Reality Toolbox